STUDI LITERATUR: PERBANDINGAN SISTEM PENDIDIKAN DASAR INDONESIA DAN FINLANDIA DALAM PERSPEKTIF GLOBAL - Rizqina Anjarwati; Nina Kumalasari; Elisa Novita Fiky Megantari; Beny Lukitoaji (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
The quality of a country's human resources is largely determined by its basic education. Each nation establishes an educational system that is specific to its unique social, cultural, and national political environment. Although Indonesia is still working on educational reforms to enhance the quality of learning at the foundational level, Finland is well-known throughout the world for having one of the greatest education systems. Through a literature review with a global viewpoint (Kemdikbud, 2020; Law No. 20 of 2003), this article aims to analyze and contrast the fundamental education systems in Finland and Indonesia. A number of variables will be contrasted, such as the curriculum, the role of instructors, instructional strategies, the learning environment, assessment procedures, and educational policy. According to the results of this research, the implementation of basic education in both nations is significantly impacted by differences in social context and policy. Indonesia continues to struggle with issues related to quality equity, curriculum load, and learning evaluation, whereas Finland prioritizes high-quality equity, trust in teachers, and student-centered learning. The goal of this research is to serve as a guide for the creation of fundamental education policy in Indonesia.